Patient preferences for facility-based management of hypertension and diabetes in rural Uganda: a discrete choice experiment - Robert Kalyesubula; Isaac Ssinabulya; Rachel Nugent; Christine Ngaruiya; Nicola L Hawley; Dallas Wood; Baylah Tessier-Sherman; Deron Galusha; Mari Armstrong-Hough; Sarah EG Moor; Andrew K Tusubira; Ann R Akiteng; et al. (BMJ Open)
Objective To explore how respondents with common chronic conditions—hypertension (HTN) and diabetes mellitus (DM)—make healthcare-seeking decisions.Setting Three health facilities in Nakaseke District, Uganda.Design Discrete choice experiment (DCE).Participants 496 adults with HTN and/or DM.Main outcome measures Willingness to pay for changes in DCE attributes: getting to the facility, interactions with healthcare providers, availability of medicines for condition, patient peer-support groups; and education at the facility.Results Respondents were willing to pay more to attend facilities that offer peer-support groups, friendly healthcare providers with low staff turnover and greater availabilities of medicines. Specifically, we found the average respondent was willing to pay an additional 77 121 Ugandan shillings (UGX) for facilities with peer-support groups over facilities with none; and 49 282 UGX for 1 month of medicine over none, all other things being equal. However, respondents would have to compensated to accept facilities that were further away or offered health education. Specifically, the average respondent would have to be paid 3929 UGX to be willing to accept each additional kilometre they would have to travel to the facilities, all other things being equal. Similarly, the average respondent would have to be paid 60 402 UGX to accept facilities with some health education, all other things being equal.Conclusions Our findings revealed significant preferences for health facilities based on the availability of medicines, costs of treatment and interactions with healthcare providers. Understanding patient preferences can inform intervention design to optimise healthcare service delivery for patients with HTN and DM in rural Uganda and other low-resource settings.